IMMU-18. Targeting Antigen Presenting Cells to improve virotherapy efficacy in Diffuse Midline Gliomas. (3rd June 2022) - Labiano, Sara; Marco-Sanz, Javier; Laspidea, Virginia; Garcia-Moure, Marc; Puigdelloses, Montserrat; Ausejo, Iker; Hernández-Osuna, Reyes; Becher, Oren; Patiño-Garcia, Ana; Gomez-Manzano, Candelaria; Fueyo, Juan; Alonso, Marta M
Abstract: With a 2-year survival less than 20%, Diffuse Intrinsic Pontine Glioma (DIPG) is the principal cause of pediatric death. Despite recent advances in the current treatments, the outcome for children with DIPGs remains dismal. Since the approval of T-VEC for melanoma by the FDA, oncolytic adenoviruses have emerged as a promising therapeutic strategy for brain tumors. Thus, our group launched the first world clinical trial phase I with the oncolytic adenovirus Delta-24-RGD (DNX-2401 in the clinic) for newly diagnosed DIPG (NCT03178032), which has shown safety and feasibility. Despite DNX-2401 increases the recruitment of T cells into the tumor, they usually become inactive due to the non-responsive tumor microenvironment evidencing the urgent need to improve this strategy focusing on the generation of effective long-term immune responses. Therefore, we decided to combine the Delta-24-RGD with the targeting of the costimulatory molecule CD40 in immunocompetent mice bearing orthotopic DIPG. The activation of the CD40 receptor, which is expressed by antigen presenting cells (APC) such as microglia, macrophages, and dendritic cells, is known to increase antigen presentation and enable T-cell priming and activation. Here, we observed that in addition to Delta-24-RGD anti-tumor effects, the stimulation of CD40 (using an agonistic antibody) on the tumor APCs results in a remodeling of the tumor immune compartment towards a proinflammatory scenario and a more efficient T-cell infiltration. Of importance, the combination therapy extends survival of treated mice as compared to single treatments or non-treated mice. In addition, we observe a complete regression of tumors in more than 40% of treated mice and the development of long-term anti-tumor immunity. We believe that these results provide a translational breakthrough in the treatment of these lethal tumors and open the door for a future innovative clinical trial.